Exposure-response relations among laboratory animal workers exposed to rats. - Nieuwenhuijsen, M; Putcha, V; Gordon, S; Heederik, D; Venables, K; Cullinan, P; Newman-Taylor, A (2003)
AIM: To explore exposure-response relations in a cohort of laboratory animal workers. METHODS: Exposure-response modelling was carried out in a cohort of 342 laboratory animal workers. Three exposure indices, divided into different exposure categories, were used in the analyses: intensity of exposure to rat urinary aeroallergen (RUA, the main allergen workers were exposed to), weekly duration of exposure to rats, and the product of the intensity and weekly duration of exposure. Outcomes studied were work related chest, eyes and nose, and skin symptoms that had started after employment at the sites, specific sensitisation, and a combination of symptoms and sensitisation. Cox proportional hazard modelling was used to explore exposure-response relations. Smoking, atopic status, age, and gender were taken into account. RESULTS: We observed the clearest exposure-response relations for the intensity of exposure to RUA and the various endpoints. No clear exposure-response relations were observed for the weekly duration of exposure or the product of the intensity and weekly duration of exposure. The strongest and clearest exposure-response relations for symptoms were observed among rat sensitised workers, while the non-sensitised workers only showed small increased risks of developing symptoms without clear exposure-response relations. Sensitised workers were almost four times more likely to go on to develop chest symptoms compared to non-sensitised workers.